FIGURATIVE LANGUAGE IN THE DIALOGUE OF MAPPETTU ADA (MARRIAGE PROPOSAL) IN BUGINESE CULTURE - Musfira Musfira (Elite : English and Literature Journal, 2021)
The objectives of the research are to explain the kinds of figurative language and the meaning of figurative language used in the dialogue of mappettu ada (Buginese term) in Buginese culture. The method used in this research was a descriptive qualitative method. The data is collected in two ways, they were observation and interview. There are some words or sentences involving figurative language in the dialogue of marriage proposal in Buginese culture. It probably hard for the readers and the listener to understand the content of the dialogue. Hence, the writer explained the meaning of the dialogue into ordinary language. This study shows that the writer found out five kinds of figurative language expressions in the dialogue of mappettu ada (buginese term) in Buginese culture, particularly in Bonenese culture. They are hyperbole, symbol, personification, metaphor, and litotes. Figurative language which often emerges in the dialogue of mappettu ada are hyperbole and symbol.